2019
DOI: 10.1155/2019/2758262
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of UCP2 Expression Protects against LPS-Induced Oxidative Stress and Apoptosis in Cardiomyocytes

Abstract: Uncoupling protein 2 (UCP2) has a cardioprotective role under septic conditions, but the underlying mechanism remains unclear. This study aimed at investigating the effects of UCP2 on the oxidative stress and apoptosis of cardiomyocytes induced by lipopolysaccharide (LPS). First, LPS increased UCP2 expression in cardiomyocytes in a time-dependent manner. LPS increased the production of lactate dehydrogenase (LDH), reactive oxygen species (ROS), and malondialdehyde (MDA) and decreased the level of superoxide di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…The impact of UCP2 on mitochondrial morphology of the brain tissue after cerebral ischemia and reperfusion has not been reported. Several studies have demonstrated that silencing UCP2 by small interference RNA resulted in more severe mitochondrial swelling, vacuolization and loss of matrix content in cardiomyocytic H9C2 cells and astrocytes compared with control cells challenged with sepsis [47,52,53]. These results support our finding that UCP2 plays an important role in maintaining mitochondrial dynamic and morphological integrity in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…The impact of UCP2 on mitochondrial morphology of the brain tissue after cerebral ischemia and reperfusion has not been reported. Several studies have demonstrated that silencing UCP2 by small interference RNA resulted in more severe mitochondrial swelling, vacuolization and loss of matrix content in cardiomyocytic H9C2 cells and astrocytes compared with control cells challenged with sepsis [47,52,53]. These results support our finding that UCP2 plays an important role in maintaining mitochondrial dynamic and morphological integrity in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…Inside cell and mitochondria, the harmful effects of ROS include structural changes in DNA and RNA, peroxidation of membrane phospholipids (composed of polyunsaturated fatty acids) and oxidation of cellular proteins that perform numerous functions inside the cell. It is therefore important to keep ROS levels at physiological values, preventing them from increasing and triggering the expression of the mitochondrial protein UCP2 on its inner membrane [ 61 ]. The uncoupling protein (UCP) family acts as a proton channel or transporter, housed in the mitochondrial inner membrane.…”
Section: Oxidative Phosphorylation and Mitochondrial Uncouplingmentioning
confidence: 99%
“…However, at 13 weeks of age (Figure 4(G)) thermally conditioned rabbit in both breeds had overexpressed hepatic UCP2 compared to their control groups indicating a protective function of this overexpression and improve thermotolerance acquisition resulted from thermal conditioning at early life. The substantial role of UCP2 is to monitor mitochondria-derived ROS production (Sreedhar and Zhao 2017) and the upregulation of UCP2 may reduce ROS production due to its antioxidative protective effects (Huang et al 2019;Migliaccio et al 2019). Besides, UCP2 overexpression may enhance cytoprotection by alleviating oxidative stress (Mattiasson et al 2003) and attenuating superoxide production to protect hepatic damage in mice due to oxidative stress (Zhang et al 2003).…”
Section: Contrasting Responses Of Nzw and Bb Rabbits Due To Thermal Conditioning At 42 Day Of Agementioning
confidence: 99%